Examining socio-demographics and understanding business factors among plastic bottle waste collectors in Ogun state, Nigeria - Solaja Oludele M.; Fielding Alistair J.; Awobona Samuel (Reciklaža i Održivi Razvoj)
This study examines the socio-demographic and economic experiences of plastic bottle waste (PBW) collectors and traders in Ijebu-Ode, Ogun State, through surveys. The study uses livelihood theory for context. The study shows that educational qualification, family size, religion, marital status, and age are more associated with PBW collection, while religion, gender, and age are more conducive to understanding the knowledge and attitudes of people who collect PBW for profit. Civilization, modern culture and consumption patterns, population, technology and industrial growth have influenced waste generation and collection for most people. Low recycling rates, inefficient waste disposal measures, and lack of knowledge about waste recycling hinder the collection of municipal waste and the development of the business. To improve the economic and social welfare of collectors and traders and reduce the impact of PBW on the environment, facilities and measures to formalize the business are advocated.